United States Protocol: The Guide to Official Diplomatic Etiquette - French, Mary Mel (Rowman & Littlefield Publishers, 2010)
United States Protocol is a must-have reference for communicating with government and business officials, international organizations, and high-level military personnel, both in the United States and abroad. Everything you need is presented in a comprehensive, detailed, and well-organized book that makes it easy to navigate official protocol. Former President Bill Clinton says in his foreword that it is 'an authoritative user's manual for international relations, it promises to become an indispensable reference_not only for those in Washington, but for all Americans in contact with people in other nations.' Ambassador Mary Mel French uses her personal experience as a former Chief of Protocol to give us the most up-to-date and user-friendly guide to diplomatic protocol at the international, national, and state level. She includes meticulous instructions, in-depth diagrams and tables, a comprehensive table of contents, and a plethora of examples that make United States Protocol the perfect guide to any official event.